2015
DOI: 10.1080/10489223.2015.1115051
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling linguistic competence by facilitating performance

Abstract: This dissertation looks at the question of whether the source of language learners' poor performance is a deficit in knowledge or a performance problem. Two constructions are examined, both being cases in which learners have been reported to show deficits in linguistic competence: (1) Korean OSV (e.g., Elmo-lul Big Bird-ka anayo. 'Elmo, Big Bird is hugging.'), where knowledge of both scrambling and case markers is necessary for target performance; (2) the English tough construction (English TC; e.g., The doll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…We would like to thank Kamil Deen, Theres Gru ¨ter, William O'Grady, Homin Sohn, all our participants, and three anonymous Second Language Research reviewers for their very helpful comments and discussions. Some findings in this study have been reported in K Kim's (2014) unpublished doctoral dissertation. All remaining errors are our own.…”
Section: Acknowledgmentssupporting
confidence: 76%
“…We would like to thank Kamil Deen, Theres Gru ¨ter, William O'Grady, Homin Sohn, all our participants, and three anonymous Second Language Research reviewers for their very helpful comments and discussions. Some findings in this study have been reported in K Kim's (2014) unpublished doctoral dissertation. All remaining errors are our own.…”
Section: Acknowledgmentssupporting
confidence: 76%
“…Previous research shows that this increased complexity can pose greater challenges for child speakers compared to NQ-NP agreement in canonical sentences (e.g., Suzuki & Yoshinaga, 2013). In particular, the scrambled word order in Korean is known to present considerable difficulties for nonnative speakers (e.g., K. Kim, 2014;Song et al, 1997), which may have been the case for our L2 participants.…”
Section: Self-paced Readingmentioning
confidence: 80%
“…English CC is one aspect of a person's competence that allows him to capture and interpret the meaning and purpose of English communication in certain contexts (Avgousti, 2018;Suvorova et al, 2021). English CC lies in a combination of linguistic competence, sociolinguistic competence, discourse competence, and communication-strategic competence or communication strategies (CSs) (Bataineh et al, 2013;Dossey et al, 2020;Fuller et al, 2018;Kim, 2016;Quasthoff & Wild, 2014).…”
Section: Introductionmentioning
confidence: 99%